Effect of “Tell Show Do” Method on Dental Anxiety in Pediatrics Dentistry: A Meta Analysis - Cahyani, Mey Ditaputri; Widyaningsih, Vitri; Prasetya, Hanung; Simatupang, Nanda Agustian (Indonesian Journal of Medicine, 2024)
Background:  Anxiety in children will make it difficult for dentists to perform dental treatment. In dentistry, especially pediatric dentistry, children who are very anxious will avoid examinations and refuse dental treatment. This study aims to analyze the influence of the "tell show do" method in reducing dental anxiety in pediatric patients. Subjects and Method:  This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: Google Scholar, PubMed, and Springer Link by selecting articles published in 2016 and 2022. The keywords used are (“tell show do” OR “TSD”AND “dental anxiety” OR “anxiety” ) AND (“pediatric dentistry” OR “children”) AND (“RCT” OR “randomized control trial”). The inclusion criteria were full paper articles using the Randomized Controlled Trial (RCT) research method, the results of the analysis used the Mean SD value, the intervention provided was a tell show do, the study subjects were pediatric dental patients at the first visit, with dental anxiety as an outcome. Articles that met the requirements were analyzed using the Revman 5.3 application. Results:  The meta-analysis of 12 articles shows that there is an increasing effect using the tell show do method on reducing dental anxiety. Children who received the tell show do intervention had a dental anxiety level 0.54 units lower than those who did not receive the tell show do, and the effect was statistically significant (SMD 0.54; 95% CI= 0.23 to 0.85; p=0.0007). Conclusion:  The tell show do method has an effect on reducing anxiety in pediatric dental patients.   Keywords: tell show do, dental anxiety, meta-analysis